Pengembangan Lembar Kerja Peserta Didik Berbasis Stem Untuk Menumbuhkan Berpikir Kreatif Siswa Pada Materi Sistem Peredaran Darah Manusia Kelas VIII SMP N 1 Pancur Batu - Irene Monyca; Juniar Hutahaean (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2024)
This study aims to determine the feasibility level of the STEM-Based LKPD to improve students' creative thinking skills on the human circulatory system material, to find out the students' responses to the STEM-Based LKPD to improve students' creative thinking skills on the human circulatory system material, and to know the effectiveness of STEM-based LKPD to improve students' creative thinking skills on the human circulatory system material. This type of research is development research (R&D) with the 4D model. Product trials include large group trials consisting of 30 students. The instruments used in this research were a validation sheet by material, learning and design experts, as well as a test in the form of a description of 10 questions to measure creative thinking skills on the material of the human circulatory system. The results of this study indicate that the developed worksheets are very feasible to use to improve students' creative thinking skills based on the assessments of material experts, learning experts, and design experts with consecutive average scores: 94.5%, 91.5% and 97.5% with very decent criteria. The developed LKPD also received a decent response from students with the results obtained in large groups of 87% and was effective in improving students' creative thinking skilla, with average result pretest is 29.92 and an average posttest result is 85.92 with an average N-Gain of 0.80 with a high interpretation.